Sosialisasi Kesiapsiagaan Dan Penanganan Pasca Bencana Gempa Bumi Pada Siswa Sekolah Menengah Pertama - Mandala, Gia Cinta; Lado, Ketrin P; W. Malana, Lestari Wirawati; Usfal, Veronika Findy; M Abe, Welfrani (Yayasan Inspirasi El Burhani, 2024)
Introduction: An earthquake is a condition that occurs when the earth vibrates or shakes as a result of the collision of tectonic plates, faults, volcanic activity, or the collapse of rocks. From the Godstats Web it shows that Indonesia is at number 2 with countries that frequently experience earthquakes from 2000 to 2024. Method: The aim of this service activity is to provide a comprehensive understanding of earthquakes, their causes and impacts. Teach preventive steps before, during, and after an earthquake. Results: This PKM activity was held for 1 (one) day, namely September 24 2024 at SMPN Satap Oeoko, Modosinal Village, North West Rote District. The area used in schools is the classroom. Conclusion: The target of service is 1 class of students at SMPN Satap Oeoko class IX.